Iäkkäiden ihmisten mielipaikat sekä niiden yhteys masennusoireistoon – eroavatko iäkkäät omaishoitajat heistä, jotka eivät toimi omaishoitajina - Hämeenaho, Katja (2025)
Hämeenaho, K. 2025. Favorite places of elderly people and their connection to depressive symptoms – do elderly caregivers differ from those who are not caregivers. Faculty of Sport and Health Sciences, University of Jyväskylä, Master's Thesis in Gerontology and Public Health, 54 pp.